2017
DOI: 10.26872/jmes.2017.8.12.480
|View full text |Cite
|
Sign up to set email alerts
|

Wear Performance of Thermally Sprayed NiCrBSi and NiCrBSi-WC Coatings Under Two Different Wear Modes

Abstract: Thermal spraying is one of the most widely used techniques of surface treatment against wear and corrosion. Especially, flame spraying process due to its advantages, such as its being more economical, easier to implement and more adaptable to a wide range of materials. However, mechanical performances are not always satisfactory because of high porosity, cracks and weaker adhesion. To obtain hard wear and corrosion-resistant coatings, the most suitable materials are those like Nickel, Cobalt-based alloys, hard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 15 publications
0
5
0
1
Order By: Relevance
“…The NiCrBSi is made of a Ni-rich solid solution phase -Ni and low content of Ni-Ni3B eutectic [29]. When the spraying alloy solidified from high temperature, several possible borides, carbides, and silicates may be created, such as Ni2B, CrB, Ni5Si3, Ni13Si12, Ni3Si, (Cr,Fe)7C3 and Cr23C6 [30]. In accordance with the above mentioned, nickel compounds were observed in both coatings, the nickel solid solution (bright areas) is visible in Figs.…”
Section: Resultsmentioning
confidence: 99%
“…The NiCrBSi is made of a Ni-rich solid solution phase -Ni and low content of Ni-Ni3B eutectic [29]. When the spraying alloy solidified from high temperature, several possible borides, carbides, and silicates may be created, such as Ni2B, CrB, Ni5Si3, Ni13Si12, Ni3Si, (Cr,Fe)7C3 and Cr23C6 [30]. In accordance with the above mentioned, nickel compounds were observed in both coatings, the nickel solid solution (bright areas) is visible in Figs.…”
Section: Resultsmentioning
confidence: 99%
“…The studies conducted by Praveen et al [29] found out that the composite coating of 60wt.%NiCrSiB-40wt.%Al 2 O 3 on AISI304 protected the surface at both 30 • and 90 • impact angles when eroded at 450 • C in hot air medium along with alumina erodent particles. However, the research work on wear performance of NiCrBSi and NiCrBSi-WC coatings on mild steel conducted by Rachidi et al [30] indicated that WC reinforcement did not cause the reduction in wear but improved its hardness. The findings of the studies conducted by Natarajan et al [31] indicated that there was significant volume and wear loss of coatings when graphite was added.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, considerable attention has been paid. Rachidi et al [31] prepares NiCrBSi and NiCrBSi-WC coatings by oxyacetylene flame spraying-their results show that the NiCrBSi coating with 60% WC has significantly high hardness (1200 HV) which is almost twice that of the NiCrBSi coatings. Zhu et al [32] studied the effect of different WC contents on the high-temperature wear behavior of NiCrBSi/WC coatings.…”
Section: Introductionmentioning
confidence: 99%